Old age and gender in popular soap operas. Arguments for a proposal of a soap opera on active aging through educational entertainment - Pérez García, Martha Estela (2020)
The literature of aging explores the deterioration of the human body, while feminist literature explores the problems of gender equality. According to Miguel Sabido (1989) and Albert Bandura (1989), the media, particularly the telenovelas, tend to use stereotypes that portray women and the elderly population negatively. Sabido uses the concepts of education and entertainment to unveil how telenovelas teach societal behavior, allowing a path for social discrimination towards them. Through these concepts, the researchers have demonstrated how the Mexican and Colombian telenovelas negatively portrayed the elderly people, especially women. Such analysis was not done in vain, as it had the purpose of giving agency to the elderly by allowing them to have to power of how they want to be represented in the media.